Human papillomavirus type 18/16 infection and prevalence among middle-aged and older Chinese rural women: a cross-sectional survey in Wufeng, Hubei Province. Issue 10 (26th November 2019) - Yu, Qiuli; Liu, Qing; Gao, Yanduo; Gong, Huiyun; Tan, Xiaodong; Zhang, Min; Tuo, Jiyu; Zhang, Yuling; Xiang, Qunying; Deng, Fenghua; Liu, Guiling
ABSTRACT: This study aimed to measure the prevalence and potential factors related to HPV 16/18 infection among middle-aged and older Chinese rural women. The study was conducted among women aged 35–65 years in rural villages within Wufeng in Hubei Province. Data were collected using a pretested questionnaire between July and August 2015. Cervical specimens were collected for HPV DNA detection and typing by using careHPV. Pearson's Chi-square and logistic regression analyses were used to examine associations with HPV positivity. Among 1001 participants, the prevalence of HPV 18/16 positive genotyping was 15.88% (n = 159). Husbands' extramarital sex (adjusted odds ratio [OR] = 15.85, 95% confidence interval [CI] 5.76–43.59), cervicitis (adjusted OR = 9.27, 95% CI 5.06–16.99), condom usage (adjusted OR = 0.16, 95% CI 0.05–0.53), higher average number of live births (adjusted OR = 1.98, 95% CI 1.32–2.96 for two live births; adjusted OR = 3.29, 95% CI 1.39–7.81 for three or more live births) were associated with HPV infection. The prevalence of HPV infection among participating women from rural areas was higher than that in several other areas in China. Our findings can aid efforts to prevent HPV infection to lower the risk of cervical cancer.